2022
DOI: 10.3390/su142416395
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of Sustainability, Board Characteristics, and Firm-Specifics on Firm Value: A Comparative Study of the United Kingdom and Turkey

Abstract: The study aims to investigate the effect of several sustainability indicators on firms’ value. Panel data of 1914 observations from the UK and Turkey from 2016 to 2021 with a fixed effect model are used to estimate the results. The findings reveal that ESG indicators associate significantly with firms’ value. However, ESG indicators exhibit a stronger significant association with Tobin’s Q than stock prices and market-to-book value. This indicates that sustainability indicators are linked to the firm’s overall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 85 publications
1
5
1
1
Order By: Relevance
“…Furthermore, the study revealed that higher levels of environmental performance and ESG scores were associated with an increased level of environmentally friendly production. In another related study, Almaqtari et al [ 43 ] revealed a significant association between ESG indicators and a firm's value, particularly Tobin's Q. The results of this research indicate that a firm's sustainability indicators are linked to the overall and the long-term market valuation.…”
Section: Literature Reviewsupporting
confidence: 55%
“…Furthermore, the study revealed that higher levels of environmental performance and ESG scores were associated with an increased level of environmentally friendly production. In another related study, Almaqtari et al [ 43 ] revealed a significant association between ESG indicators and a firm's value, particularly Tobin's Q. The results of this research indicate that a firm's sustainability indicators are linked to the overall and the long-term market valuation.…”
Section: Literature Reviewsupporting
confidence: 55%
“…It is common knowledge that independent directors are knowledgeable individuals who can oversee management, monitor it, and offer sage counsel and recommendations about social transparency (Khaireddine et al 2020). According to Almaqtari et al (2022), the body of existing literature indicates that board committee independence has a beneficial impact on sustainability reporting. A substantial favorable association between board independence and social reporting was also reported by Aliyu (2019).…”
Section: Board Committee Independence and Sustainability Reportingmentioning
confidence: 99%
“…. (Gregory et al, 2014;Hussain et al, 2018;Orazalin and Mahmood, 2021 (Haque and Ntim, 2018;Govindan, 2021;Orazalin and Mahmood, 2021;Lu, 2021;Almaqtari et al,2022 (Velte, 2020;Albitar et al, 2020;Qureshi et al, 2020;Rossi et al, 2021;Govindan et al, 2021;Almaqtari et al, 2022 (Farag et al, 2014;Li et al, 2021;Rossi et al, 2021 (Post et al, 2011;Frias-Aceituno et al, 2013;Liao et al, 2015;Aguilera et al, 2015;Burke et al, 2019;Brennan, 2020 (Fuzi et al, 2016;Liao et al, 2019;Pasko et al, 2021 and Diab, 2018;Kim et al, 2018;Sampong et al, 2018;Velte, 2020;Harun et al, 2020;Rossi et al, 2021;Govindan et al, 2021;Abdi et al, 2022;Friske et al, 2022;Huang, 2022 (Bajic and Yortoglu, 2018;Hu et al, 2018;WAHYUDI, 2018;Borghesi et al, 2019;Harun et al, 2020;Noor et al, 2020;Seok et al, 2020;…”
Section: ‫البحث‬ ‫ممخص‬unclassified